2014
DOI: 10.12669/pjms.304.5444
|View full text |Cite
|
Sign up to set email alerts
|

Computer Based Assessment (CBA): Perception of residents at Dow University of Health Sciences

Abstract: Background and objective : During the past few years, Computer-based assessment (CBA) has gained popularkity as a testing modality. This assessment offers several advantages over paper based assessment (PBA) testing. The objective of this study was to find out residents’ perception of this method of assessment. Methods : The post graduate residents of Dow University of Health Sciences in the field of Surgery, Medicine, Gynecology and Obstetrics experienced their first formative Computer-based assessment (CBA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 7 publications
3
33
0
Order By: Relevance
“…More studies present results concerning the students' perception on e-assessment using MCQ namely Hogdson & Pang [7], Jawaid, Moosa, Jaleel & Ashraf [8], and Walker, Topping & Rodrigues [9]. Those studies revealed that the students have a positive opinion about e-assessment in general and about MCQ in particular.…”
Section: Introductionmentioning
confidence: 94%
“…More studies present results concerning the students' perception on e-assessment using MCQ namely Hogdson & Pang [7], Jawaid, Moosa, Jaleel & Ashraf [8], and Walker, Topping & Rodrigues [9]. Those studies revealed that the students have a positive opinion about e-assessment in general and about MCQ in particular.…”
Section: Introductionmentioning
confidence: 94%
“…In postgraduate residents in surgery, medicine, gynaecology and obstetrics high initial scepticism concerning eLearning (76.4%) was contrasted by high satisfaction rates after the eLearning experience (64.8%) and the majority of residents rated eLearning as better than traditional learning methods (61.8%) [23]. The above-mentioned randomised study among primary care physicians revealed similarly high satisfaction rates for eLearning and traditional learning methods, which is in agreement with most of the literature on this topic [39].…”
Section: Satisfaction With Elearningmentioning
confidence: 99%
“…Computer-based testing does not only mean moving questions from paper to screen (Jawaid, Moosa, Jaleel, & Ashraf, 2014;Lee, 2009). Essentially, computerbased tests should use advantages of technology as much as possible and support the quality of the tests in various ways (Wirth, 2008).…”
Section: Computer-based Testingmentioning
confidence: 99%
“…In a study by Hosseini et al (2014), it was found that students had more positive attitudes towards computer-based tests when compared to paper-based tests. Another study among postgraduate students reported that 61.8% preferred computer-based tests compared to paper-based tests (Jawaid et al, 2014). In terms of test scoring, although some studies reported equivalent results for both computer and paper-based tests (Mason, Patry & Berstein, 2001), there are some other studies that claimed the computer-based test as a reason for better scoring (DeAngelis, 2000).…”
Section: Computer-based Testingmentioning
confidence: 99%